PENGARUH GOOD GOVERNANCE, KOMPETENSI, KOMITMEN ORGANISASI, DAN TEAMWORK TERHADAP KUALITAS LAPORAN KEUANGAN DI PEMERINTAH KABUPATEN SRAGEN - Yuniatin Wardani; Darmawan Fitriyanto (Universitas Ahmad Dahlan, 2019)
This study aims to determine the influence of good governance, competence, teamwork, and organizational commitment to the quality of local financial statements. The research was conducted at 62 (sixty two) Regional Device Work Unit in Sragen Regency Government. The sample used by a number of population is 8 PPKD and 54 PPK-SKPD in Sragen Government Environment. The results showed that there was a significant influence between good governance (X1), competence (X2), organizational commitment (X3), and team work (X4) simultaneously to the quality of regional financial report (Y). So from the results of the study concluded that the quality of district financial statementsPartially, good governance has a significant effect, while competence, commitment and teamwork have no significant effect on the quality of local financial statements. The adjusted value of R2 is 0.515. This means that 51.5% of the variation in the quality of regional financial statements can be explained by the variation of the four independent variables of good governance, competence, organizational commitment, and teamwork. While the remaining 48.5% is explained by other causes outside the research model